Kyphoplasty as a Treatment Option for Traumatic Burst Fractures: A Case Series Evaluating Patient Outcomes and Functional Benefits - Anoop S. Chinthala; Barnabas Obeng-Gyasi; Trenton A. Line; Matthew K. Tobin; Gordon Mao; Bradley N. Bohnstedt (Brain Sciences)
Background/Objectives: Kyphoplasty and vertebroplasty are minimally invasive approaches for spinal fractures aiming to reduce pain, increase mobilization, and prevent further vertebral height loss. Their efficacy in treating burst fractures has been questioned due to fragment mobility and concerns for cement leakage. We aim to report outcomes in patients who underwent kyphoplasty for spinal burst fractures. Methods: We conducted a retrospective review of patients with burst fractures treated from 2018 to 2023. Those who underwent kyphoplasty or vertebroplasty and had follow-up imaging were included. Clinical characteristics and follow-up outcomes were obtained through chart review. The primary outcome was the need for surgical intervention after kyphoplasty. Results: We identified ten patients (mean age 67.9 years, range 36–93 years) with burst fractures who underwent kyphoplasty/vertebroplasty. Six received kyphoplasty/vertebroplasty within 1 week of injury and four between 1 and 4 months post-injury. Nine patients had a TLICS score of 2, and one had a TLICS score of 5. Kyphoplasty/vertebroplasty was performed for pain management in seven patients and significant/worsening vertebral height loss in three patients. At follow-up, 70% of patients reported an improvement in pain and 75% of patients reported improved mobility. One patient experienced progression of an L2 burst fracture but improved with conservative management. No patient required additional surgical fixation. Conclusions: In this series of ten patients with spinal burst fractures, standalone kyphoplasty was a safe and effective treatment. Our findings suggest kyphoplasty may be a viable treatment option for select spinal traumatic burst fractures, offering potential pain relief and mobility improvement in the short term.